European position paper on the management of patients with patent foramen ovale. General approach and left circulation thromboembolism - Pristipino, Christian; Sievert, Horst; D’Ascenzo, Fabrizio; Louis Mas, Jean; Meier, Bernhard; Scacciatella, Paolo; Hildick-Smith, David; Gaita, Fiorenzo; Toni, Danilo; Kyrle, Paul; Thomson, John; Derumeaux, Genevieve; et al. (European heart journal, 2019)
Abstract The presence of a patent foramen ovale (PFO) is implicated in the pathogenesis of a number of medical conditions; however, the subject remains controversial and no official statements have been published. This interdisciplinary paper, prepared with involvement of eight European scientific societies, aims to review the available trial evidence and to define the principles needed to guide decision making in patients with PFO. In order to guarantee a strict process, position statements were developed with the use of a modified grading of recommendations assessment, development, and evaluation (GRADE) methodology. A critical qualitative and quantitative evaluation of diagnostic and therapeutic procedures was performed, including assessment of the risk/benefit ratio. The level of evidence and the strength of the position statements of particular management options were weighed and graded according to predefined scales. Despite being based often on limited and non-randomised data, while waiting for more conclusive evidence, it was possible to conclude on a number of position statements regarding a rational general approach to PFO management and to specific considerations regarding left circulation thromboembolism. For some therapeutic aspects, it was possible to express stricter position statements based on randomised trials. This position paper provides the first largely shared, interdisciplinary approach for a rational PFO management based on the best available evidence.